THE IMPLEMENTATION OF INNOVATION PERFORMANCE TOWARDS EMPLOYEE INVOLVEMENT AT PT ISTANA DELI KENCANA MEDAN - Darwan Tanady; Agus Susanto; Bestadrian P. Theng; Benny Lim (Journal of Innovation Research and Knowledge, 2022)
The company has expectation in higher levels of employee motivation, creativity, productivity, and commitment that will move the organization forward with greater profitability. Organizations operating with the involvement of their employees, have developed the employee‘s involvement to actively seeking their contribution to the decision making process. The employee that can create good innovation want to increase the involvement in the company in order to give contribution to the company‘s development. The purposes of this research is to know whether the innovation performance has impact to employee involvement at PT Istana Deli Kencana Medan. Research design used in this research is descriptive research design and correlational research design. Research methods which used are descriptive statistic analysis, validity and reliability test, normality test, coefficient correlation, coefficient of determinant, simple linear regression analysis and Z testing. The sample size in this research is 112 employees. The result of this research is that there is impact innovation performance towards employee involvement at PT Istana Deli Kencana Medan. Based on Z test, it can obtained that Z-count > Z-table (9.88 > 1.96). It means the hypothesis is accepted that innovation performance has impact towards to employee involvement in PT Istana Deli Kencana Medan. From correlation test, it can be know that innovation performance has strong positive relationship toward employee involvement in 0.934. Coefficient determinant is 87.3%. It means that changing of employee involvement can be explained by innovation performance while the rest as 12.7% can be explained by other factors. From the regression linear equation, it can be obtained the regression equation Y = 1.080 + 0.697X. The regression coefficient of innovation performance is 0.697. It means that innovation performance has positive impact to employee involvement. The increasing 1 unit of innovation performance can increase employee involvement in 0.697 unit.